Efecto del tiempo de recocido en una fundición nodular astm a536 sobre la resistencia a la tracción, tensión de fluencia, ductilidad, dureza y microestructura - Custodio Bobadilla, Luis Miguel (2019)
In this investigation, the effect of the annealing time in an ASTM A536 nodular cast iron on the tensile strength, yield stress, ductility, hardness and microstructure was studied. For this reason, cylindrical bars with a diameter of 15 mm x 200 mm in length manufactured by the company Foundry to Laminate SAC - Lima were used. They were annealed at 880 ° C at times of 5, 10, 15, 20, 25, 30 and 35 hours with slow cooling (inside the furnace). The specimens were machined from the annealed bars, for the tensile test according to ASTM E8-98 and for the hardness test according to ASTM E-140. The experimental results show that the increase of the annealing time causes the tensile strength to decrease from 492.00 MPa for 5 hours to 312.00 MPa for 35 hours. The yield stress decreases from 334.70 MPa for 5 hours to 263.00 MPa for 35 hours and with respect to ductility, it increases from 8.10% for 5 hours to 18.50% for 25 hours. Then it decreases slightly to 15.70% for 35 hours, this due to the decomposition of austenite into ferrite. The microstructural results show that for the times of 5, 10, 15 and 20 hours the decomposition of the austenite to ferrite is partially and microstructurally of ferrite, some of pearlite and graphite (Gn); while for all 25, 30 and 35 hours the transformation of austenite to ferrite is totally and microstructurally consists of ferrite, and graphite nodules (Gn), characteristic of a ferritic nodular function. It is also established that the minimum annealing time at 880 ° C for obtaining a ferritic nodular cast iron is 25 hours and that with the graphite (Gn) in any treatment always stable. It is concluded that the annealing time at 880 ° C with slow cooling, significantly affects the tensile strength, yield stress, ductility and hardness, and the microstructure in a nodular cast iron ASTM A536, according to the statistical analysis with 95% reliability